2019
DOI: 10.1063/1.5098057
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced upper critical field in Co-doped Ba122 superconductors by lattice defect tuning

Abstract: Nanoscale defects in superconductors play a dominant role in enhancing superconducting properties through electron scattering, modulation of coherence length, and correlation with quantized magnetic flux. For ironbased superconductors (IBSCs) that are expected to be employed in high-field magnetic applications, a fundamental question is whether such defects develop an upper critical field (Hc2) similar to that of conventional BCS-type superconductors. Herein, we report the first demonstration of a significantl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Therefore, these powders are suitable for ex situ synthesis route. Transport and magnetic measurements confirmed that Tc of the Co-Ba122 sample is 26.3 K [25,34].…”
Section: Methodsmentioning
confidence: 72%
“…Therefore, these powders are suitable for ex situ synthesis route. Transport and magnetic measurements confirmed that Tc of the Co-Ba122 sample is 26.3 K [25,34].…”
Section: Methodsmentioning
confidence: 72%
“…Based on the lattice parameters, we estimate that the K-doping levels of the samples sintered at 600°C and 650°C, which showed nearly single phase, were ∼42%. Note that x a and x c are rough estimations because lattice parameters of the samples prepared via high-energy ball milling are affected by lattice defects ( Tokuta and Yamamoto, 2019 ). Based on the EDX, the K-doping levels of the samples sintered at 600°C, 700°C, and 900°C were ∼38%, which is close to the nominal composition.…”
Section: Resultsmentioning
confidence: 99%
“…At 5 K under self-field conditions, the J c value of these bulks improved to a value approximately three times that reported in a previous study ( Tokuta et al., 2020 ). Furthermore, the H c2 value of Co-doped Ba122 polycrystalline bulks can be artificially enhanced and adjusted by introducing lattice defects into the grains via high-energy ball milling ( Tokuta and Yamamoto, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One takes it to be an intrinsic degradation due to an suppression of superfluid density and J c at misoriented grain boundaries (GBs) 27 – 29 , while the other invokes various extrinsic factors like cracks or impurities segregated to the GBs 30 , 31 . Since there is evidence for both effects, the importance of careful synthesis and understanding of the processing conditions is becoming increasingly important 8 , 32 34 .…”
Section: Introductionmentioning
confidence: 99%